2022
DOI: 10.1021/acs.jpclett.2c01908
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation Dynamics of a Carbon Dioxide Dication Produced by Ion Impact

Abstract: The response of carbon dioxide to radiolysis is crucial for understanding the atmospheric chemistry of planets. Here, we present a combined experimental and theoretical investigation of the three-body fragmentation dynamics of CO 2 2+ to C + + O + + O initiated by 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In their study on the bond rearrangement of CO 2 molecules, Zhao et al [13] reported a branching ratio of 0.0796 ± 0.0058%, among all the fragmentation channels of the dication following strong field ionization of the neutral CO 2 molecules. In another study, Yuan et al [19] reported a 1.7% branching ratio of the C + + O + 2 channel fragmenting into C + + O + + O. Other than these two studies, to the best of our knowledge, the branching ratio for this channel is not mentioned anywhere else.…”
Section: Branching Ratiomentioning
confidence: 86%
See 1 more Smart Citation
“…In their study on the bond rearrangement of CO 2 molecules, Zhao et al [13] reported a branching ratio of 0.0796 ± 0.0058%, among all the fragmentation channels of the dication following strong field ionization of the neutral CO 2 molecules. In another study, Yuan et al [19] reported a 1.7% branching ratio of the C + + O + 2 channel fragmenting into C + + O + + O. Other than these two studies, to the best of our knowledge, the branching ratio for this channel is not mentioned anywhere else.…”
Section: Branching Ratiomentioning
confidence: 86%
“…To date, all the reported studies have centered on light-molecule interactions for molecular oxygen production. Notably, there is one study, to the best of our knowledge, by Yuan et al [19], in which the authors reported on molecular oxygen formation due to ion-molecule interaction. They observed O + 2 coinciding with C + upon a 1 keV/u Ar 2+ beam.…”
Section: Introductionmentioning
confidence: 99%